(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To determine the prevalence of fungal contamination and fungal composition in traditional herbal medicines at Nghe An Traditional Medicine Hospital in 2023. Subjects and methods: A cross-sectional descriptive study was conducted, examining 170 traditional herbal medicines from Nghe An Traditional Medicine Hospital covered by hazardous substance insurance. The techniques used in the study were: fungal culture in Sabouraud medium; identification of gene types by morphological sequencing and PCR using ITS1, ITS4, ITS5, and NL4 genes. Automated sequences were compared with international genbank to determine the type. Keywords: Medicinal plants, fungi. Results and conclusions: The fungal infection rate was 32.9%. The highest infection rate was found in medicinal herbs derived from roots (40.3%); followed by those from branches, leaves, flowers, and fruits at 32.08%. 50 samples were infected with 1 fungal species, 5 samples with 2 fungal species, and 1 sample with 3 fungal species. 63 fungal strains belonging to 16 species were identified, with 61 samples having identified species and 2 samples remaining unidentified. 28 samples (44.44%) were infected with Aspergillus, comprising eight species, with A.niger being the most prevalent (15.87%); 35 samples (55.56%) were infected with other fungal species, comprising eight species. 6 genera were identified: Aspergillus, Rhizopus spp, Penicillium spp, Fusarium spp, Phoma sp, and Cladosporidium.